La imagen del monarca en la comedia "El villano en su rincón" - Gómez, Jesús (El Colegio de México, 2011)
The avalaible scholarship has generated a number of different interpretationsof Lope de Vega’s El villano en su rincón: this article puts forwardan analysis of the play’s political and ideological implications within theparadigm of the Court, which was the main model of organization and governmentof premodern Europe. Given the centrality of monarch in Lope’scomedias, a happy ending is provided for the dramatic conflict (arisingfrom the peasant’s voluntary isolation) when Juan Labrador, following kingLudovico’s wishes, becomes a member of the Court.